Promotion of ultra-processed foods in Brazil: combined use of claims and promotional features on packaging - Giovanna Calixto Andrade; Laís Amaral Mais; Camila Zancheta Ricardo; Ana Clara Duran; Ana Paula Bortoletto Martins (Universidade de São Paulo, 2023)
ABSTRACT OBJECTIVE To assess the availability of different promotional strategies applied for UPF sales in Brazilian food retailers. METHODS Information available on food packaging was gathered from all packaged products sold in the five largest food retail chains in Brazil in 2017. UPF were identified using the NOVA food classification system. From this sample, data related to promotional characteristics, nutrition claims and health claims were collected and coded using the INFORMAS methodology. Additional claims referring to the Brazilian Dietary Guidelines were also collected. RESULTS This study evaluated the packaging of 2,238 UPF, of which 59.8% presented at least one promotional strategy. Almost one third denoted a simultaneous use of different promotional strategies in the same packaging. Nutrition claims were the most commonly found promotional strategy, followed by health claims and the use of characters. The food subgroups comprising the highest prevalence of promotional strategies on their labels were: noncaloric sweeteners (100.0%), breakfast cereals and granola bars (96.2%), juices, nectars and fruit-flavoured drinks (92.9%), other unsweetened beverages (92.9%), and other sweetened beverages (92.6%). CONCLUSIONS Considering the poor nutritional quality of UPF, the widespread presence of promotional features on their packaging highlights the need for marketing restrictions on this kind of product.